Gino Severini in Switzerland: A Technical Study of the Wall Paintings of Saint Nicolas de Myre in Semsales. (17th February 2023) - Iazurlo, Paola; Piqué, Francesca; Moretti, Patrizia
ABSTRACT: Although Gino Severini is recognised as a leading exponent of European avant-garde movements through the first half of the twentieth century, his work as a mural painter is little known. This article reports the technical study of Severini's wall paintings for the Swiss church of Saint Nicolas de Myre in Semsales (1924–1926), in the framework of a research project coordinated by the University of Applied Sciences and Arts of Southern Switzerland and financed by the Swiss National Science Foundation. Taking an interdisciplinary approach, the project investigates the wall paintings made by the artist in five churches in Switzerland and dating between 1924 and 1947, with the aim of clarifying the artist's mural painting techniques. Following research in the parish archives and in those of the Severini family, the project proceeded in the different churches with in situ examination (diffuse and raking visible light, UV radiation, digital microscopy) supported by non-invasive scientific investigation (technical photography and spectroscopic point analyses) and laboratory invasive analyses on micro-samples. Lastly, the data from all the various sources are collected and interrelated. The artist's first commission, in 1924 at Semsales, became the longest and most complex, given the artist's relative lack of mural experience, the extent of surfaces, and variety of techniques adopted. The investigation reveals a long process in which Severini mastered a secco procedures using organic binders, on plasters that had already been applied, flanked by works in the tradition of a fresco painting, enriched with a modern palette of colours. Underlying all this work was a long process of planning, in which the artist associated the differing techniques with variations in style, in an extremely personal language between cubism and classicism.